The spacing of births and women's subsequent earnings: Evidence from a natural experiment - Arizo Karimi (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2014)
This paper analyzes the consequences of the spacing of births for women's subsequent labor income and wages. Spacing births in longer intervals may allow women to re-enter the labor market between childbearing events, thereby avoiding expanded work interruptions and, in turn, reducing the negative effects of subsequent children. Based on arguably exogenous variation in birth spacing induced by pregnancy loss between the first two live births, the evidence provided in this paper supports this hypothesis and suggest that delaying the second birth by one year, on average, increases the probability of re-entering the labor market between births. Moreover, spacing births are found to increase both labor market participation and labor income over a long time period after second birth. Also long-run wages are positively affected, with a more pronounced effect for highly educated mothers.
Keywords: J31; J13; 330; Child spacing; Female wages; Female lifetime earnings; Natural Experiment